2007
DOI: 10.1007/s00249-007-0242-3
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dynamics of the antifungal molecules Syringotoxin-B and Syringopeptin-25A from molecular dynamics simulation

Abstract: The phytopathogen Pseudomonas syringae pv. syringae produces toxic cyclic lipodepsipeptides (CLPs): nona-peptides and syringopeptins. All CLPs inhibit the growth of many fungal species, including human pathogens, although different fungi display different degrees of sensitivity. The best studied CLPs are Syringomycin-E (SR-E), Syringotoxin-B (ST-B) and Syringopeptin-25A (SP-25A). Their biological activity is affected by membrane composition and their structural differences. We previously (Matyus et al. in Eur … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…These findings provided information about the hydrophilic character of these molecules [14]. Different properties such as chemical structure, critical micellar concentration and antimicrobial activity have been studied for other P. syringae metabolites such as syringopeptins, syringomicins, corpetin and arthrofactin [15][16][17].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…These findings provided information about the hydrophilic character of these molecules [14]. Different properties such as chemical structure, critical micellar concentration and antimicrobial activity have been studied for other P. syringae metabolites such as syringopeptins, syringomicins, corpetin and arthrofactin [15][16][17].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…NMR investigations in aqueous solution showed that SP25A assumes a conformation having distinct structural portions, e.g. a loop region (amino acids 2-6), a left-handed helical region (amino acids [8][9][10][11][12][13][14][15], and an octadepsipeptide moiety (amino acids [18][19][20][21][22][23][24][25] that resembles the seam of a tennis ball [3,4]. Syringopeptins have phytotoxic, antifungal and antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have been demonstrated to be a suitable technique to evaluate conformational ensemble of disordered peptides which consists of a variety of conformations [28][29][30][31]. In the this contribution, we present a molecular dynamics (MD) investigation of NPs in solution starting from their structure bound to the NPR-C [21,23] with the aim of providing a high-resolution atomistic view of their conformational ensemble in solution and of specific interactions that cannot be easily captured by experimental techniques [32][33][34].…”
Section: Introductionmentioning
confidence: 99%